CeRNA profiling and the role in regulating gonadal development in gold pompano - Changcan Yang; Yijun Zhao; Wendong Zhao; Hai Huang; Quanqi Zhang; Jinxiang Liu (BMC Genomics)
Abstract Background The golden pompano (Trachinotus ovatus) is an economically significant warm-water aquaculture species in China. The time required for sexual maturity of T. ovatus is relatively long. Consequently, it has prompted researchers to investigate gonadal development process of this fish. To gain further insight into the function of competing endogenous RNA (ceRNA) in the gonads of T. ovatus and the regulatory mechanism of the ceRNA network, whole transcriptome libraries were constructed from the testes and ovaries. Results Overall, a total of 96 differentially expressed microRNAs (DE-miRNAs), 2,338 differentially expressed messenger RNAs (DE-mRNAs), 973 differentially expressed long non-coding RNAs (DE-lncRNAs), and 94 differentially expressed circular RNAs (DE-circRNAs) were identified. Additionally, a ceRNA network was constructed, and enrichment analysis confirmed the involvement of numerous pathways in reproduction and gonadal development, including the TGF-β signaling pathway and GnRH signaling pathway. The ceRNA network analysis revealed that the oni-let-7d-1-p3 and PC-3p-112794_13 may play significant roles in T. ovatus gonadal development. And we have observed a possible relationship related to gonadal development involving R-spondin-1 (Rspo1), oni-let-7d-1-p3, and MSTRG.14909.1 (lnc-TGFβR). Dual-luciferase gene reporter system and fluorescence in situ hybridization analyses preliminary verified the regulation relationship between Rspo1 and oni-let-7d-1-p3, as well as lnc-TGFβR and oni-let-7d-1-p3 in the cytoplasm of sertoli cells. Conclusion It is hypothesized that the lnc-TGFβR functions as a sponge for oni-let-7d-1-p3, participating in regulating the process of testis development. These findings could enhance our understanding of ncRNAs in gonadal development. It also provides new insight into the function of ncRNAs and the regulatory relationship of ceRNA between males and females. These results might contribute to discussions on the regulation of ncRNA during gametogenesis.